Aliran Mu’tazilah Dalam Pemikiran Teologi Islam: Sejarah, Pemikiran, dan Implikasinya Terhadap Perkembangan Pemikiran Islam - Fahmi Al Munawwar; Imamuddin Zenggi; Aldiansyah Pane; Zulfahmi Lubis (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The Mu’tazilah school is an Islamic theological movement that positions reason as the primary instrument for understanding religion, particularly regarding the reason-revelation dialectic, human free will, and divine justice. This study aims to examine the historical emergence of the Mu’tazilah, evaluate its core doctrines, and analyze its influence on Islamic theology. Employing a qualitative approach with a library research design, this study conducts text analysis on primary and secondary sources. The findings indicate that the Mu’tazilah emerged as a response to early Islamic theological-political conflicts, rigidly structured around five core principles (al-uṣūl al-khamsah): divine unity, divine justice, the promise and threat, the intermediate position, and enjoining good and forbidding evil. Scientifically, this rationalism contributed fundamentally to laying the methodological groundwork for systematic Islamic theology (ilm al-kalam) and philosophy. However, this research is limited by its broad library-based scope, which does not explore specific manuscript variations or the granular doctrinal shifts between the Basra and Baghdad factions. Therefore, future research is recommended to pursue comparative studies among internal Mu'tazilah figures and analyze the relevance of 'Neo-Mu'tazilism' to modern discourses. In conclusion, despite facing heavy criticism, Mu'tazilah's rationalism remains a resilient intellectual pillar in Islamic theology.